2018
DOI: 10.17159/2413-3221/2018/v46n1a430
|View full text |Cite
|
Sign up to set email alerts
|

Extension officers' perception towards accreditation and regulation of extension services in North West Province, South Africa

Abstract: This paper examines extension officers' perception towards accreditation and regulation of extension services. This is based on the premise that a pluralistic extension service delivery currently prevails in South Africa where public and private service providers exist with differentials in quality of services to clients; which can be overcome through accreditation of providers from end-users' perspectives. Using a random sampling technique, 69 extension officers were sampled and a questionnaire was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
2
1
1
Order By: Relevance
“…The effects of the independent variables used to estimate the logit regression were presented using coefficients and P-values signs of each dependent variable. This study's findings were consistent with Verbeeck [22] and Shemfe and Oladele [11] reported that access to extension and cooperative management has a positive and significant impact on the yield of coffee production. Both access to research and cooperative management affects the quality and quantity of coffee yield without interference from other factors.…”
Section: Institutional Factors Affecting Optimization Of Coffee Produsupporting
confidence: 90%
See 2 more Smart Citations
“…The effects of the independent variables used to estimate the logit regression were presented using coefficients and P-values signs of each dependent variable. This study's findings were consistent with Verbeeck [22] and Shemfe and Oladele [11] reported that access to extension and cooperative management has a positive and significant impact on the yield of coffee production. Both access to research and cooperative management affects the quality and quantity of coffee yield without interference from other factors.…”
Section: Institutional Factors Affecting Optimization Of Coffee Produsupporting
confidence: 90%
“…The findings showed that most study participants at 57.1% were not attending plant clinics to optimize coffee production against 42.9% who were attending ( Table 2). This study's findings concur with those of Shemfe and Oladele [11], who reported that despite governments and other NGOs' efforts to introduce training to farmers, including plant clinics, the majority of the respondents did not attend. Most of the farmers established that the meetings were a waste of time as there were claims that some extension officers disseminated misleading and incorrect information to farmers.…”
Section: Access To Extensionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the study, the probit regression model is used because it is the standard method for estimating binary category dependent variables following [40]. The dependent variable was the development of entrepreneurship based on the commercialisation index created.…”
Section: Inferential Statisticsmentioning
confidence: 99%